The Possibility of a Phenomenology of Cultural Worlds in Hegel and Husserl. Issue 1 (10th January 2017) - Staehler, Tanja
Abstract: The world we live in proves best understood as a cultural world. Cultural worlds are examined in this article regarding their aesthetic and ethical dimensions, with the help of Hegel and Husserl. The ethical realm is characterized by a tension between ethical conscience and cultural norms. Even Hegel, who is often conceived as a philosopher of customs, explores the significance of conscience in a detailed phenomenology. Husserl provides a curious perspective on ethics when he, under the heading of a renewal (Japanese Kaizo ) of reason, provides an account of a vaguely dialectical development of reason as logos which goes beyond the division between the 'descriptive' and 'ethical'. In the wider sense of ethics, it is also 'good' to write about the world we live in. Literature (Hermann, Wallace) will be treated here as an exemplary art-form that stands in close proximity to philosophy since both strive to capture in language the world we live in.